2012
DOI: 10.1007/s11102-012-0450-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk of thromboembolic events in patients with prolactinomas compared with patients with nonfunctional pituitary adenomas

Abstract: Prolactin has been proposed as a potent coactivator of platelet aggregation, possibly contributing to thromboembolic events. The objective of the study was to evaluate the relationship between prolactinoma and deep vein thrombosis (DVT), pulmonary embolism (PE), and cerebrovascular accident (CVA). Subjects were identified from a prospectively maintained pituitary database at the Cleveland Clinic. We retrospectively reviewed the charts of 544 subjects: 347 patients with prolactinomas (prolactinoma group) and 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…PRL concentration also correlates with tumor size [5, 116]. A serum PRL level >200–250 ng/ml is usually due to a macroadenoma (>1 cm in diameter), rather than a microadenoma (<1 cm diameter) [116, 117]. In the event of a macroprolactinoma, the PRL concentration can even rise to values as high as 35,000 ng/ml (see Table 2).…”
Section: Diagnosis Of Hyperprolactinemia (Hprl)mentioning
confidence: 99%
“…PRL concentration also correlates with tumor size [5, 116]. A serum PRL level >200–250 ng/ml is usually due to a macroadenoma (>1 cm in diameter), rather than a microadenoma (<1 cm diameter) [116, 117]. In the event of a macroprolactinoma, the PRL concentration can even rise to values as high as 35,000 ng/ml (see Table 2).…”
Section: Diagnosis Of Hyperprolactinemia (Hprl)mentioning
confidence: 99%
“…They found that platelet activity during pregnancy was comparable to non-pregnant state, therefore no significant effect of PRL on platelet function in vivo was observed. Mon SY et al [20] did not find a significant rate of deep vein thrombosis, pulmonary embolism and cerebrovascular accidents in prolactinoma patients. According to these results they concluded that hyperprolactinemia per se did not appear to predispose to hypercoagulable state.…”
Section: Discussionmentioning
confidence: 89%
“…demonstrated that hyperprolactinaemia in pregnancy was not associated with increased in vivo platelet activity and counts . Similarly, Mon et al . reported that they did not observe a higher rate of thromboembolic events in patients with prolactinoma compared to controls.…”
Section: Discussionmentioning
confidence: 93%